The effects of short‐term and long‐term exposure to extreme cold environment on the body's physiological responses: An experimental study. Issue 2 (9th September 2018) - Saedpanah, Keivan; Aliabadi, Mohsen; Motamedzade, Majid; Golmohammadi, Rostam
Abstract: There is little epidemiological data to make reliable conclusions about the effects of exposure to cold on the body's physiological responses. The current study aimed to address this lacuna in the available research. The study sample consisted of 50 outdoor mechanic workers as a case group and 15 staff members as a control group used in the outdoor automechanic workshops. Air environmental factors, including dry‐bulb temperature and air velocity, were measured by the portable hot wire thermo anemometer in the workstation of each subject. The body's physiological responses were also measured during daily activities in accordance with ISO 9886. Using Semmes–Weinstein monofilament, touch sensory tests were conducted for determining hands' sensorineural functions. The baseline measurements showed the mechanic workers had lower finger sensation levels and finger skin temperatures than the control group ( p  < 0.05). This may be attributed to long‐term exposure to acute cold air during cold seasons. However, after short‐term exposure to extreme cold environment, the mechanic workers showed lower losses in finger skin temperatures and finger sensation levels than the control group ( p  < 0.05). The findings confirmed that prolonged localized cold exposure among mechanic workers can result in localized habituation of vasoconstrictor responses.